Embryonic Stem Cell-Derived Exosomes Attenuate Transverse Aortic Constriction Induced Heart Failure by Increasing Angiogenesis - Pang, Yanan; Ma, Minglu; Wang, Dong; Xia, Jiacun; Wang, Xinyue; Hou, Lei; Wang, Zhiguo; Li, Xun (Frontiers in Cardiovascular Medicine, 2021)
Background: Although there are concerns regarding their clinical use, embryonic stem cells (ESCs) hold a great promise for cardiac repair. Exosomes deriving from ESCs constitute a promising alternative for heart restoration. However, their effects in hypertension-induced heart failure are still unknown. Objective and Methods: To investigate the effects of ESCs-derived exosomes on hypertension-induced heart failure and the underlying mechanisms, sustained transverse aortic constriction (TAC) was performed on 8-week-old C57BL/6 male mice. After 1 months, ESCs-derived exosomes were isolated and injected intravenously once a week for 6 weeks. Echocardiography, wheat germ agglutinin (WGA), Masson staining, immunohistochemistry, and tube formation assays were all involved in our study. Results: Proteomics analyses revealed that ESC-derived exosomes contain FGF2 protein. Tube formation induced by these exosomes could be inhibited by FGF2R siRNA interference. ESCs-derived exosomes evidently attenuated TAC-induced heart failure, improving cardiac function and promoting myocardial angiogenesis which can be attenuated by selective FGF2 inhibitor AZD4547. Conclusions: ESC-derived exosomes attenuate TAC-induced heart failure mostly by promoting myocardial angiogenesis. FGF2 signaling plays a vital role in the myocardial angiogenesis induced by ESC-derived exosomes.